P260 A Model For Bridging The Translational Valley Of Death In Spinal Cord Injury. (15th August 2013) - Barrable, B; Thorogood, N; Noonan, V; Joshi, P; Stephenson, K; Kwon, B; Dvorak, M
Abstract : Background: Despite the amount of funding that supports basic research, few research discoveries achieve their potential. The transition from bench-to-bedside research is so fraught with obstacles that it is referred to as the "valley of death". Objective: The Rick Hansen Institute (RHI) developed a unique Praxis Model for translational research in the field of spinal cord injury (SCI). At RHI this means bringing knowledge into action; to improve healthcare outcomes for people with SCI and decrease the financial impact on the healthcare system. Methods: The research continuum begins with discovery science which feeds into the knowledge cycle, continues with the acceptance and uptake into the treatment of spinal cord injuries. The core activity within the Praxis Model is a knowledge cycle that consists of a four-phased strategy: 1) Environmental scan, 2) Knowledge generation and synthesis, 3) Knowledge validation, and 4) Implementation. Results: RHI has participated and supported over 60 studies since 2007 and engaged researchers from nine countries, 46 academic institutions and various accreditation and professional associations. Currently, the model is being independently evaluated to determine strengths and limitations. Examples of RHI initiatives using the Praxis Model and results of the evaluation will be presented. Discussion: RHI has developed an innovative solution to move knowledge into action. The Praxis Model strives to lead collaboration across the global SCI community by providing funding, infrastructure, strategic partnerships, governance and a network. Implications: Lessons learned in developing the Praxis Model may assist other organisations dealing with similar translational research challenges.